2008
DOI: 10.1080/02688690801894646
|View full text |Cite
|
Sign up to set email alerts
|

A case of brain abscess due toEntamoebaspecies,Eikenella corrodensandPrevotellaspecies

Abstract: We report a case of brain abscess due to multiple pathogens including Entamoeba species, Eikenella corrodens and Prevotella species. Patient had odontogenic infection without any site of amoebic infestation. Complete recovery was achieved with surgical treatment and antimicrobial therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…[26] Other group of patients at risk of unusual pathogens are the immigrants from underdeveloped countries, they can have, in addition to those pathogens affecting inmunocompromised patients, other pathogens like Taenia, E. histolytica, Schistosoma, Echinococcus, and Paragonimus. [26,[65][66][67][68][69][70][71] In the Nathoo et al [4] series (the biggest reported), it was found that majority of patients undergoing surgery (53.2%) had isolation of a single organism, being the commonest the gram-positive organisms: S. aureus and Staphylococcus epidermidis, especially in traumatic BA. Streptococcus milleri isolates were predominant in patients with paranasal sinusitis, whereas Proteus mirabilis was most commonly isolated in otogenic infections.…”
Section: Etiologymentioning
confidence: 99%
“…[26] Other group of patients at risk of unusual pathogens are the immigrants from underdeveloped countries, they can have, in addition to those pathogens affecting inmunocompromised patients, other pathogens like Taenia, E. histolytica, Schistosoma, Echinococcus, and Paragonimus. [26,[65][66][67][68][69][70][71] In the Nathoo et al [4] series (the biggest reported), it was found that majority of patients undergoing surgery (53.2%) had isolation of a single organism, being the commonest the gram-positive organisms: S. aureus and Staphylococcus epidermidis, especially in traumatic BA. Streptococcus milleri isolates were predominant in patients with paranasal sinusitis, whereas Proteus mirabilis was most commonly isolated in otogenic infections.…”
Section: Etiologymentioning
confidence: 99%